2020
DOI: 10.1039/c9sc06442g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unsymmetrically substituted triarylamines via acceptorless dehydrogenative aromatization using a Pd/C and p-toluenesulfonic acid hybrid relay catalyst

Abstract: An efficient and convenient procedure for synthesizing triarylamines based on a dehydrogenative aromatization strategy has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“… Notably, in this transformation, the enantiomeric retention ratio of N -arylated amino acids increased as the steric hindrance of the α-position increased (Scheme ). In addition to our research work, there are many key achievements utilizing such a formal oxidative coupling strategy to synthesize aryl amine , in terms of developing a broader scope of amines or using other homogeneous/heterogeneous catalytic systems and transition-metal-free protocols, by the groups of Yoshikai, Lemaire, , Deng, Nozaki/Mizuno/Yamaguchi, Stahl, , Hayashi, and Maycock . Leonori et al also reported a recent update of using a photochemical approach to realize the formal oxidative coupling of cyclohexanones with amines to build anilines …”
Section: Formal Oxidative Couplingmentioning
confidence: 85%
See 2 more Smart Citations
“… Notably, in this transformation, the enantiomeric retention ratio of N -arylated amino acids increased as the steric hindrance of the α-position increased (Scheme ). In addition to our research work, there are many key achievements utilizing such a formal oxidative coupling strategy to synthesize aryl amine , in terms of developing a broader scope of amines or using other homogeneous/heterogeneous catalytic systems and transition-metal-free protocols, by the groups of Yoshikai, Lemaire, , Deng, Nozaki/Mizuno/Yamaguchi, Stahl, , Hayashi, and Maycock . Leonori et al also reported a recent update of using a photochemical approach to realize the formal oxidative coupling of cyclohexanones with amines to build anilines …”
Section: Formal Oxidative Couplingmentioning
confidence: 85%
“…71 adding p-toluenesulfonic acid (TsOH) as an additive. 45 Besides, recently our group disclosed that valuable carbazoles could be synthesized by the double aminations of biphenols with ammonia (Scheme 17). 72…”
Section: Formal Reductive Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding TsOH as an additive was a key in this reaction, and the authors proposed that TsOH could not only help the condensation of cyclohexanone with aryl amines but also promote the dehydrogenation process to produce triarylamine products (Scheme 202). 340 Other notable examples have also been reported by the groups of Deng, 341−344 Yoshikai, 345 Nozaki/ Mizuno, 346−351 Hayashi, 352 and Stahl. 353,354 In 2015, Li's group successfully merged the reductive dearomatization of phenol with the reductive amination process of cyclohexanones with amines to utilize phenols as cyclohexyl synthons to build N-cyclohexyl amines, and such a transformation could also be carried out in a flow reactor (Scheme 203).…”
Section: Phenols and Aryl Ethers Utilized As Cyclohexyl Synthonsmentioning
confidence: 99%
“…Adding TsOH as an additive was a key in this reaction, and the authors proposed that TsOH could not only help the condensation of cyclohexanone with aryl amines but also promote the dehydrogenation process to produce triarylamine products (Scheme ). Other notable examples have also been reported by the groups of Deng, Yoshikai, Nozaki/Mizuno, Hayashi, and Stahl. , …”
Section: Formal Functionalization Of Phenols Anisoles and Diaryl Ethe...mentioning
confidence: 99%